2023
DOI: 10.1177/21582440231188308
|View full text |Cite
|
Sign up to set email alerts
|

Leading Generation Z’s Financial Literacy Through Financial Education: Contemporary Bibliometric and Content Analysis in China

Liu Hong Shan,
Kenny S. L. Cheah,
Serrene Leong

Abstract: There is a growing awareness of the importance of financial education and literacy in personal economic success, yet not many Generation Z are proficient in this area. The lack of understanding can lead to consequences such as not recognizing the need for greater retirement savings, making poor spending decisions, or when overpaying off high-interest debt. In addition, many of the studies on financial education and literacy among Generation Z remain untapped in the context of China. As a result, the researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…This indicates a level of intentionality and awareness in their financial decision-making process. However, it is fundamental to enhance and develop age-appropriate financial literacy programs focusing on independent financial decision-making as financial education influences their financial selfbeliefs and their ability to set clear financial goals for the future (Shan, 2023). Table 6.…”
Section: Weighted Mean 405 Verbal Interpretation Great Extentmentioning
confidence: 99%
“…This indicates a level of intentionality and awareness in their financial decision-making process. However, it is fundamental to enhance and develop age-appropriate financial literacy programs focusing on independent financial decision-making as financial education influences their financial selfbeliefs and their ability to set clear financial goals for the future (Shan, 2023). Table 6.…”
Section: Weighted Mean 405 Verbal Interpretation Great Extentmentioning
confidence: 99%
“…A survey reveals that this age is more likely than older age groups to have been targeted in an impersonation scam and swayed to provide personal or financial information (UKFinance, n.d.). Furthermore, according to the National Association of Plan Advisors (NAPA) in the United States, Gen Z has the lowest level of financial literacy, with only 28 percent of questions correctly answered on average (Hong Shan et al, 2023). Data also showed that Generation Z has the lowest level of financial literacy among Gen X, boomers, and millennials, given their young ages (Csiszar, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Generation Z refers to the second-youngest generation, born between 1997 and 2012, with millennials preceding them and the alpha generation following them. Most of this generation is financially vulnerable (Hong Shan et al, 2023). Generation Z has a strong desire to enjoy experiences.…”
Section: Introductionmentioning
confidence: 99%